Taking Place : Location and the Moving Image - Gorfinkel, Elena; Rhodes, John David, 1969- (Book collections on Project MUSE., 2011)
Taking Place argues that the relation between geographical location and the moving image is fundamental and that place grounds our experience of film and media. Its original essays analyze film, television, video, and installation art from diverse national and transnational contexts to rethink both the study of moving images and the theorization of place. Through its unprecedented-and at times even obsessive- attention to actual places, this volume traces the tensions between the global and the local, the universal and the particular, that inhere in contemporary debates on global cinema, telev.